0D, 1D, 2D, and 3D simulations of an idealized coaxial impedance-matched Marx generator - D. V. Rose; W. A. Stygar; D. T. Offermann; K. R. LeChien; M. G. Anderson; K. S. Raman; A. E. Schmidt; D. A. Max; C. B. Beatty; R. M. Anaya; A. S. Anquillano; A. Arsenlis; et al. (Physical Review Accelerators and Beams)
We have conducted 0D, 1D, 2D, and 3D simulations of an idealized coaxial impedance-matched Marx generator (IMG) [Phys. Rev. Accel. Beams 20, 040402 (2017)PRABCJ2469-988810.1103/PhysRevAccelBeams.20.040402]. The 0D calculations were conducted with a four-element circuit model; the 1D, 2D, and 3D calculations were conducted with highly resolved, fully electromagnetic representations. The IMG consists of 30 stages distributed axially and connected electrically in series. Each stage is powered by two bricks separated by 180° and connected electrically in parallel. Each brick comprises two opposite-polarity capacitors in series with a single switch. The bricks drive an internal impedance-matched coaxial transmission line terminated by a resistive load. The simulations neglect effects due to the switch-triggering circuit, the capacitor-charging circuit, external conducting boundaries, and reactive components of the load. We find dimensionality does not significantly affect the electrical power delivered by the IMG to its load: peak load powers estimated by the 0D, 1D, 2D, and 3D simulations agree to within 1%. The 3D calculations demonstrate that electromagnetic power radiated by the bricks, and axial gaps between stages, reduces the peak load power by less than ∼1%. Each simulation assumes the load impedance is 34% above that at which the load power is maximized. Operating an IMG with such an overmatched load offers several advantages while decreasing the peak load power by only 2%. The 0D, 1D, 2D, and 3D models outlined herein could be adapted to assess computationally competing IMG designs, and conduct a variety of numerical IMG experiments, before an IMG is constructed.